Reduced expression of alpha-1,2-mannosidase I extends lifespan in Drosophila melanogaster and Caenorhabditis elegans. - Liu, Y.L.; Lu, W.C.; Brummel, T.J.; Yuh, C.H.; Lin, P.T.; Kao, T.Y.; Li, F.Y.; Liao, P.C.; Benzer, S.; Wang, H.D. (Aging Cell, 2009)
Exposure to sub-lethal levels of stress, or hormesis, was a means to induce longevity. By screening for mutations that enhance resistance to multiple stresses, we identified multiple alleles of alpha-1,2-mannosidase I (mas1) which, in addition to promoting stress resistance, also extended longevity. Longevity enhancement is also observed when mas1 expression is reduced via RNA interference in both Drosophila melanogaster and Caenorhabditis elegans. The screen also identified Edem1 (Edm1), a gene downstream of mas1, as a modulator of lifespan. As double mutants for both mas1 and Edm1 showed no additional longevity enhancement, it appeared that both mutations function within a common pathway to extend lifespan. Molecular analysis of these mutants revealed that the expression of BiP, a putative biomarker of dietary restriction (DR), is down-regulated in response to reductions in mas1 expression. These findings suggested that mutations in mas1 may extend longevity by modulating DR.